2021
DOI: 10.3389/fmolb.2020.605623
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA BTG3-7:1 and JUND Co-regulate C21ORF91 to Promote Triple-Negative Breast Cancer Progress

Abstract: BackgroundTriple-negative breast cancer (TNBC) is a type of highly invasive breast cancer with poor prognosis. Recently, massive data reveal that long non-coding RNAs (lncRNAs) play important roles in cancer progress. Recently, although the role of lncRNAs in breast cancer has been well documented, few focused on TNBC. In this study, we aimed to systematically identify functional lncRNAs and to explore its molecular mechanism on TNBC progress.MethodsThe recurrence of lncRNAs and their target genes were validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…These results implied that MAPK8/JNK1 and MAPK9/JNK2-NFATC2/NFAT1 pathways contribute to the signaling events intrinsic to MDA-MB-231 cells that regulate proliferation and migration. JUND is also required for TNBC progression (Ibrahim et al, 2018;Dan et al, 2020). Our results showed that EPHA2-AS1/2silencing reduced the expression of JUND, a MAPK/JNK substrate.…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 52%
“…These results implied that MAPK8/JNK1 and MAPK9/JNK2-NFATC2/NFAT1 pathways contribute to the signaling events intrinsic to MDA-MB-231 cells that regulate proliferation and migration. JUND is also required for TNBC progression (Ibrahim et al, 2018;Dan et al, 2020). Our results showed that EPHA2-AS1/2silencing reduced the expression of JUND, a MAPK/JNK substrate.…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 52%